Representation of statistical properties - Chong, Sang Chul; Treisman, Anne (Vision research (Oxford), 2003)
Everyday scenes often contain sets of similar objects. Perceptual representations may summarize these with statistical descriptors. After determining the psychological mean of two sizes, we measured thresholds for judging the mean with arrays of 12 circles of heterogeneous sizes. They were close to those for the size of elements in homogeneous arrays and single elements, and were little affected by either exposure duration (50–1000 ms) or memory delays (up to 2s). They were only slightly more accurate within the same distribution than across different distributions (normal, uniform, two-peaks, and homogeneous), confirming that subjects were indeed averaging sizes.